Local anesthesia: An appropriate technology for simple fistula repair (2007)
Objectives: To assess the efficacy of local infiltrative anesthesia with lidocaine hydrochloride in patients undergoing the surgical repair of a simple vesico-vaginal fistula. Methods: The study was carried out with 21 patients undergoing the repair of a simple midvaginal vesico-vaginal fistula. The patientsT perception of pain was evaluated intraoperatively. Results: Most patients indicated that the anesthetic agent provided adequate analgesia, and all fistulas were repaired successfully without postoperative complications. Conclusion: Repairing simple vesico-vaginal fistulas is feasible with a local infiltrative anesthetic